Symbolism and allegory in the Qur'an: Muhammed Asad's modernist translation - Chande, Abdin N. (Islam and Christian-Muslim relations, 2004)
This paper will analyze Muhammad Asad's translation of the Qurān, which provides us with the means to explore the ‘mythic’ language of sacred text. Despite its modernist agenda, it is a coherent translation which brings into sharp focus a particular modernist discourse on the Qurān. The outcome of this approach is precisely in its style of picking and choosing meanings and interpretations which best suit the modernist project. The paper provides examples of this from the translation which has extensive footnote explanations. What distinguishes its approach from that of the classical commentators? Does the Qurān contain mythical or legendary accounts, and if so, what purpose do they serve? The paper focuses on these and other questions.